Metabolity látky VUFB 15468 u zvírat - Poláková, L; Koruna, I; Ryska, M; Metysová, J; Lapka, R; Sispera, L; Svátek, E (Ceskoslovenska farmacie, 1990)
Metabolites of drug VUFB 15468 present in the urine of rats, mice and dogs and in rat faeces after peroral administration were determined qualitatively. The relative representation of the individual metabolites in the urine of rats and mice was determined radiometrically after p. o. administration of [3H]VUFB 15468. For qualitative demonstration the metabolites were extracted; they were detected, partially identified and purified by thin-layer chromatography and then analyzed by mass spectrometry and IR-spectrometry. Structures of 11 metabolites were completely or partially determined in rat urine. Five of them were also found in rat faeces, one in murine urine and five in canine urine. In all animal species also unchanged VUFB 15468 was found. For quantification of the individual metabolites and VUFB 15468, TLC-radiometry and liquid scintillation spectrometry were used in rats and mice. Of the relative representation of metabolites, about one third is unchanged VUFB 15468, the rest are metabolites. In mice, the proportion of unchanged VUFB 15468 is much higher, about two thirds.
Keywords: inbrední kmeny potkanů; Rats, Inbred Strains; Rats; psi; Dogs; mužské pohlaví; Mice; benzylaminy; Mice, Inbred Strains; inbrední kmeny myší; krysa rodu Rattus; biotransformace; Biotransformation; zvířata; Benzylamines; myši; antidepresiva; Antidepressive Agents; Male; Animals